2002
DOI: 10.1179/095066001225001085
|View full text |Cite
|
Sign up to set email alerts
|

Developing KH2PO4and KD2PO4crystals for the world's most power laser

Abstract: generating plasmas on each side of the crystal to actThe authors are at Lawrence Livermore National as high voltage electrodes. The laser beam then passes Laboratory, Livermore, CA 94551, USA (deyoreo1@ through a set of phosphate glass booster ampli ers llnl.gov).before entering the nal spatial lter. The product of this portion of the laser system is a full uence beam with a wavelength of 1053 nm. However, because the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
241
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 460 publications
(242 citation statements)
references
References 7 publications
0
241
0
1
Order By: Relevance
“…In the 1990s, the rapid growth technique was developed to grow large-scale (40-50 cm) KDP boules at a rate of 10-20 mm/day [2,3] , which was one of the seven wonders during NIF laser construction [4] . Due to a growth rate an order of magnitude faster than conventional growth, a greater number of bulk defects were formed, degrading the performance of the crystals by causing pinpoint damage and optical losses, which adversely affected the quality of the downstream beam [1,5] . It was found that typical damage pinpoints were caused by defects, which efficiently absorbed laser energy, leading to a temperature rise and subsequent 'micro-explosion' [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1990s, the rapid growth technique was developed to grow large-scale (40-50 cm) KDP boules at a rate of 10-20 mm/day [2,3] , which was one of the seven wonders during NIF laser construction [4] . Due to a growth rate an order of magnitude faster than conventional growth, a greater number of bulk defects were formed, degrading the performance of the crystals by causing pinpoint damage and optical losses, which adversely affected the quality of the downstream beam [1,5] . It was found that typical damage pinpoints were caused by defects, which efficiently absorbed laser energy, leading to a temperature rise and subsequent 'micro-explosion' [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…KH 2 PO 4 (KDP) crystals are important nonlinear optical materials in many applications, such as frequency converters and Pockel cells for high-power large-aperture laser systems [1] . In the 1990s, the rapid growth technique was developed to grow large-scale (40-50 cm) KDP boules at a rate of 10-20 mm/day [2,3] , which was one of the seven wonders during NIF laser construction [4] .…”
Section: Introductionmentioning
confidence: 99%
“…These crystals often suffer from laser damage, which adversely affect the quality of downstream beam [1]. The observed damage thresholds of KDP/DKDP crystals are much lower than the intrinsic thresholds [2].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Both potassium dihydrogen phosphate (KDP) and DKDP crystals are nature choices for National Ignition Facility (NIF) simply because of their adequate nonlinear optical properties and availability in large growth sizes. Plates of DKDP crystals are needed for the third harmonic generation (THG) in NIF for that they can effectively reduce the transverse stimulated Raman scattering (TSRS).…”
Section: Introductionmentioning
confidence: 99%